Initial investigation of three selective and potent small molecule oxytocin receptor PET ligands in New World monkeys. Issue 14 (15th July 2016) - Smith, Aaron L.; Freeman, Sara M.; Barnhart, Todd E.; Abbott, David H.; Ahlers, Elizabeth O.; Kukis, David L.; Bales, Karen L.; Goodman, Mark M.; Young, Larry J.
Graphical abstract: The oxytocin system has been implicated as being a modulator of social behavior patterns. The radiosynthesis of three oxytocin receptor selective PET ligands and their in vivo evaluation within New World monkeys are reported herein. Abstract: The neuropeptide oxytocin is part of a neuroendocrine system that has physiological effects ranging from ensuring uterine myometrial contractions at parturition and post-partum mammary gland milk ejection to the modulation of neural control of social relationships. This initial study was performed to investigate the potential use of positron emission tomography (PET) for localizing oxytocin receptors in two New World primates. Three biomarkers for PET (1 –3 ) that are known to have high affinity and selectivity for the human oxytocin receptor were investigated in the common marmoset ( Callithrix jacchus ) via PET imaging. Brain penetration, and uptake in the salivary gland area were both observed with biomarkers2 and3 . No brain penetration was observed with1, but uptake was observed more specifically in several peripheral endocrine glands compared to2 or3 . Biomarker2, which displayed the best brain penetration of the three biomarkers in the marmoset, was then investigated in the monogamous coppery titi monkey ( Callicebus cupreus ) in a brain scan and a limited full body scan. No significant brain penetration of2 was observed in the titi monkey, but significant uptake was observed in various locations throughout the periphery. Metabolism of2 was suspected to have been significant based upon HPLC analysis of blood draws, but parent compound was still present near the end of the scan. Follow-up investigations will focus on next generation biomarkers bearing improved binding characteristics and brain penetrability as well as investigating tissue in regions where biomarker uptake was observed.